Pro-Kontra Perdagangan Bebas Asean-China (ACFTA) - Nugroho SBM (Media Ekonomi dan Manajemen, 2011)
FTntries and China and such advantages can be enjoyed in the long run. While a counter claim that today's reality in ACFTA implemtation has hurt ASEAN member countries in general and Indonesia in particular. And the fact in the short term should not wait for the solution in the long run. The policy implications that can be drawn by the Indonesian government are the government needs to continue to renegotiate the products and services that are not yet ready, optimize its trade attache in China, to diversify export destinations (not just China alone), and information dissemination on various opportunities, threats, and rules in ACFTA  Keywords : ASEAN-Free Trade Arrangement, Global Trade Analysis Project, Renegotiate, Diversify Export Destination, Dissemination information